Integrating SERVQUAL and TAM to Evaluate Service Quality and User Acceptance of a Government Website - Baiq Shilla Aryoningsih; Khairul Imtihan; Mardi (Edu Komputika Journal, 2025)
This study aims to evaluate the service quality and user acceptance of a government website by integrating the SERVQUAL model and the Technology Acceptance Model (TAM). The study addresses the limited empirical evaluation of regional government websites, particularly in capturing both service-oriented and technology-based user perceptions. A quantitative approach was employed using a structured questionnaire distributed to 569 respondents who had used the Satpol PP website of Central Lombok Regency. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) combined with Importance–Performance Map Analysis (IPMA). The results indicate that assurance and reliability significantly influence perceived usefulness and perceived ease of use, which in turn affect user satisfaction and behavioral intention. The dimensions of tangibles and empathy showed weaker influence, highlighting the importance of system functionality over aesthetic or emotional design elements. The IPMA findings identify perceived ease of use and assurance as strategic priorities for improvement due to their high importance and moderate performance. This study provides contextual and methodological insights by applying an integrated SERVQUAL, TAM, IPMA framework to evaluate a local government law-enforcement website in Indonesia, a setting that has been rarely examined in prior digital service quality studies. Practically, it offers actionable recommendations for enhancing user trust, system usability, and service responsiveness in digital public platforms. These insights are expected to support the broader agenda of inclusive and sustainable digital governance at the local government level.